Formulation of the twisted-light–matter interaction at the phase singularity: The twisted-light gauge - Quinteiro, Guillermo Federico (2015)
Twisted light is light carrying orbital angular momentum. The profile of such a beam is a ring-like structure with a node at the beam axis, where a phase singularity exists. Due to the strong spatial inhomogeneity the mathematical description of twisted-light–matter interaction is non-trivial, in particular close to the phase singularity, where the commonly used dipole-moment approximation cannot be applied. In this paper we show that, if the handedness of circular polarization and the orbital angular momentum of the twisted-light beam have the same sign, a Hamiltonian similar to the dipole-moment approximation can be derived. However, if the signs differ, in general the magnetic parts of the light beam become of significant importance and an interaction Hamiltonian which only accounts for electric fields is inappropriate. We discuss the consequences of these findings for twisted-light excitation of a semiconductor nanostructures, e.g., a quantum dot, placed at the phase singularity.